Compositions, Morphological and Thermal Properties of Green Banana Flour and Starch - Pailumpa Nimsung; Masubon Thongngam; Onanong Naivikul (Agriculture and Natural Resources, 2007)
Banana (Musa sp.) is cheap and has been grown in most parts of Thailand. In its green stage, banana contains mainly carbohydrate especially starch; therefore, it is suited to use as the source of starch and flour. Banana flours and starches were investigated by using 3 Thai banana cultivars Musa (AA) sp. (Kluai Khai; KH), Musa (AAA) sp. (Kluai Hom Tong; HT), and Musa (ABB) sp. (Kluai Namwa; NW). Banana flours obtained from dried pulp, which were milled and sieved. Then banana flour (F) was used for starch isolation by using 0.05N NaOH. The KHF, HTF and NWF had yielded 48.12%, 56.50%, and 54.50% (based on whole fresh fruit), respectively. Banana flour had yielded starch (S) as followed, 30.37% (KHS; AA group), 29.67% (HTS; AAA group) and 33.18% (NWS; ABB group) (p>0.05) respectively. The chemical compositions of flours (protein, fat, and ash) were higher than those of starches as well as they were varied among cultivars. Morphology of banana starches, determined by scanning electron microscope (SEM), had smooth surface and irregular in size and shape (round, long and oblong). The pasting curves obtained by RVA of green banana flours were lower than those of green banana starches of the same varieties. The gelatinization temperature ranges obtained from differential scanning calorimetry (DSC) were 73.96-86.18°C and 70.70-81.50°C for flours and starches respectively.